Evaluation of the Community Literacy Program Family Planning Village - Setiajaya, Dea; Efriliana, Hartini; Aonilah, Ida; Kurniawati Hasibuan, Anggi (Universitas Negeri Semarang, 2022)
Literacy awareness strongly supports success in dealing with various problems. Through reading skills, a person not only gains knowledge but can document a piece of his experience as a reference in the future. This study aims to evaluate the BUCANTIK (Budayakeun Maca Sanajan Saeutik) program at the Community Reading Garden (TBM) program of Tanjung Gumulung Family Planning (KB) Village. This qualitative research method uses an online interview with the BUCANTIK program manager and Tanjung Gumulung KB Village community. The research subjects include program managers and community visitors to the BUCANTIK program in Tanjung Gumulung KB Village, totalling five informants. The results of the research were obtained using the CIPP evaluation model (context, input, process, product), namely context evaluation, regarding the BUCANTIK program manager and the low literacy interest of the Tanjung Gumulung KB Village community. Input evaluation regarding program resources in the availability of books at TBM BUCANTIK. Process evaluation regarding program implementation methods and strategies. Product evaluation regarding the program's benefits felt by the community and the expected results. Evaluating the BUCANTIK program can help program managers and the community increase community literacy interest